Trends in Overweight and Obesity in Portuguese primary school children: COSI study 2008 -2013 - Rito, Ana (2017)
Aims: To investigate trends in childhood obesity in the context of the WHO/Europe Childhood Obesity Surveillance Initiative (COSI study), in Portugal, between 2008 and 2013. Key Methods: Nutritional Status of children aged 6-8 years old, from a national representative sample in Portugal, was evaluated according to the WHO/Europe COSI study protocol in rounds 1 (2008; n=3765); round 2 (2010; n= 4064) and round 3 (2013; n= 5935). Height and weight were directly measured by trained fieldworkers. Overweight (including obesity) and obesity prevalence were calculated using the international body mass index cut-offs according to WHO criteria. Results: In 2008, 37,9% of the portuguese were overweight and 15,3% were obese with higher prevalence shown in boys than in girls (p>0,05). During the 5 year period the prevalence of childhood overweight and obesity significantly decreased by 4,3% and by 1,4%(p< 0,05), respectively. Obesity peaked in 8 year olds (boys and girls) but it was only significantly higher for girls aged 7 years old (p<0,05), in 2013. Conclusion: Trends in overweight and obesity in national representative samples of Portuguese children of the COSI study, have declined during the period 2008-2013. However, among countries of the WHO European region, Portugal continues to show one of the highest prevalence of overweight and obesity in primary school aged children suggesting that programs addressing childhood obesity have to continuously be a priority in the public health Portuguese agenda.